Dosing considerations for rufinamide in patients with Lennox–Gastaut syndrome: Phase III trial results and real-world clinical data. (April 2017) - Kothare, Sanjeev; Kluger, Gerhard; Sachdeo, Rajesh; Williams, Betsy; Olhaye, Omar; Perdomo, Carlos; Bibbiani, Francesco
Highlights: Rufinamide is an effective treatment option for Lennox–Gastaut syndrome. Low starting doses and slow titration may improve rufinamide tolerability. Clinical experience supports starting rufinamide at a dose of 5–10 mg/kg/day. Real-world data show the dose can be escalated to 15–20 mg/kg/day after 1–3 days. The authors recommend not increasing rufinamide dose if no response is noted. Abstract: Purpose: Lennox–Gastaut syndrome (LGS), a rare, severe form of childhood-onset epilepsy, is difficult to control. Rufinamide is indicated for adjunctive treatment of seizures associated with LGS in adults and pediatric patients aged ≥1 year. In clinical practice, rufinamide dosing and titration may differ from the trial setting. Here, rufinamide clinical trial data are compared with real-world experience to provide insight into optimal dosing and titration strategies. Methods: Rufinamide Phase III and open-label extension (OLE) studies were reviewed; effect of titration and dose on adverse events (AEs) and concomitant AED use were analyzed. Real-world studies of rufinamide in LGS were identified via PubMed search. Clinical data were extracted and compared. Results: Results demonstrated that a rapid titration schedule (7 or 14 days) of rufinamide was tolerable for most patients and resulted in highly significant reductions in total and tonic–atonic seizures, with efficacy and tolerability sustained over 3 years. The most common AEs during the Phase III study – somnolence, vomiting, and pyrexia – occurred during the first 3 weeks of treatment, and a small subset of patients were unable to reach target dose in that time. Use of concomitant AEDs had no clinically significant effect on plasma concentrations of rufinamide. Data from real-world clinical studies are consistent with the Phase III and OLE study results. However, relative to those used in clinical trials, lower doses and slower titration schedules were commonly employed in real-world settings. Conclusions: A lower dose and slower titration schedule ("low and slow") may reduce incidence of AEs without compromising efficacy of rufinamide in LGS.